Impact of adding glucose-coated water-soluble silver nanoparticles to the silkworm larval diet on silk protein synthesis and related properties. Issue 3 (11th February 2020) - Zhang, Yun-Hu; Shi, Mei-Juan; Li, Kai-Le; Xing, Rui; Chen, Zhuo-Hua; Chen, Xue-Dong; Wang, Yong-Feng; Liu, Xiao-Fei; Liang, Xin-Yin; Sima, Yang-Hu; Xu, Shi-Qing
Abstract: Biological modifications of the silk fibroin (silk) material have broad applications in textiles, biomedical materials and other industrial materials. It is economical to incorporate nanoparticles to the biosynthesis of silk fibroin by adding them to silkworm larval diets. This strategy may result in the rapid stable production of modified silk. Glucose-coated silver nanoparticles (AgNPs) were used to improve the AgNPs' biocompatibility, and the AgNPs were efficiently incorporated into silk by feeding. Larvae fed with AgNPs produced silk with significantly improved antibacterial properties and altered silk secondary structures. Both positive and negative effects on the growth and synthesis of silk proteins were observed after different AgNPs doses. Larvae feeding with low concentration of 0.02% and medium 0.20% AgNPs have greater transfer efficiencies of AgNPs to silk compared with feeding high concentration of 2.00% AgNPs. In addition, the elongation and tensile strength of the produced silk fibers were also significantly increased, with greater mammalian cell compatibility. The appropriate AgNPs concentration in the diet of silkworms can promote the synthesis of silk proteins, enhance their mechanical properties, improve their antibacterial property and inhibit the presence of Gram-negative bacteria. Graphical Abstract: HIGHLIGHTS: AgNPs in silkworm diets can be efficiently incorporated into silk. Dietary AgNPs can produce antibacterial silk with altered mechanical properties. A low dietary AgNPs concentration can enhance silk fibroin synthesis.